MÉTODO GLOBAL EN EL PROCESO DE LA LECTOESCRITURA EN SEGUNDO DE BÁSICA DE LA UNIDAD EDUCATIVA FE Y ALEGRÍA. PERÍODO 2018-2019 - Sailema Caguana, Katherine Yesenia (2019)
The objective of this research is to analyze the global method in the process of reading and writing in the second year of the Fe y Alegria Educational Unit, Period 2018-2019. The importance of using the global method in the process of reading and writing to achieve academic success in language and literature area is explained, as well as how the method should be applied so that children learn significantly. The application of the global method contributes to the development of cognitive, communicative, sociocultural competence and stimulates the child's interest, thus developing their innate abilities following a simple and natural process. In the theoretical framework, the benefits, characteristics, process of the global method for use in the process of reading and writing, inductive, deductive and analytical method were used, the type of research that was used is field, design of the investigation is descriptive, the research technique that was the observation with its respective instrument that was an observation type. In this way it is concluded that the global method makes the literacy process simpler and enriching where the children develop their skills and abilities.